Rapid Diagnosis of Pharyngitis Caused by Group A Streptococci - Gerber, Michael A. (American Society for Microbiology, 2004)
Although commercial rapid antigen detection tests (RADTs) are more expensive than blood agar plate (BAP) cultures, the advantage they offer is the speed with which they provide results. Rapid identification and consequent prompt treatment of patients with pharyngitis due to group A beta-hemolytic streptococci (GABHS) can reduce the risk of spread of GABHS, can allow patients to return to school or work sooner, and may reduce the acute morbidity of this illness. In most studies, RADTs have been compared with BAP cultures as the criterion standard. However, these comparisons are complicated by the fact that there is no universally accepted procedure for performing a BAP culture. The great majority of the RADTs that are currently available have a high specificity (i.e., 95% or greater) and a sensitivity of between 70 and 90% compared with BAP cultures. Few published studies have compared the performance of various RADTs to each other or examined the performance of various RADTs in the office setting. There is also relatively little published information about how physicians in practice actually use RADTs, but the available information suggests that many physicians do not follow recommended guidelines. While the development of easy-to-perform RADTs for the diagnosis of GABHS pharyngitis has altered clinical practice substantially, only limited data about cost-effectiveness are currently available.